Capital Structure, Liquidity Management And Their Impact On Profitability: A Comparative Study Of Beverage Food And Tobacco Firms And Manufacturing Firms In Colombo Stock Exchange (Cse) In Sri Lanka - Niththiya, S.; Muraleetharan, P. (Faculty of Graduate Studies University of Sri Jayewardenepura, 2015)
The Capital Structure, Liquidity Management and Profitability are very important issues in the growth and survival of the business. Therefore, this study seeks to examine Capital structure, Liquidity Management and their impact on profitability: A comparative study of Listed Beverage food and tobacco firms and Manufacturing firms in Colombo Stock Exchange (CSE) in Sri Lanka. The present study covered Listed Beverage food and tobacco firms and Manufacturing firms over the period of past 7 years from 2008 to 2014. Correlation and regression analysis were used to analyze the data. In this study, Capital structure is represented by three indicators: Debt to Equity Ratio (DE), Debt to Total Assets (DTA) and Gearing ratio (GR) while the liquidity management examined by Current ratio (CR) and Quick Ratio (QR). The profitability examined by Gross Profit Ratio (GPR), Net Profit Ratio (NPR), Return on Capital Employed (ROCE) and Return on Assets (ROA) According to the findings there is a significant impact of Capital Structure and Liquidity Management on profitability of Listed Beverage food and tobacco firms and Manufacturing firms. There is a positive relationship between capital structure and profitability and also positive relationship between liquidity management and profitability of Beverage food and tobacco firms. But there is a positive relationship between capital structure and profitability and there is a negative relationship between liquidity management and profitability of manufacturing firms. The Beverage food and tobacco firms have greater significant impact of capital structure liquidity management on profitability than manufacturing firms. Since, this research focused only two determinants of profitability as capital structure and liquidity management, so other dimensions like firm size, growth rate should also be considered for future researchers. Moreover this research study took place only in two sectors in CSE in Srilanka; therefore increasing the sample size in terms of number of firms, sectors and year could also provide more accurate and generalize results.
Keywords: Capital employed; Capital structure; Gearing ratio,; Liquidity management; Profitability